The investments of NextGenerationEU vs urban competitiveness of Italian metropolitan areas - Gargiulo, Carmela; Sgambati, Sabrina (TeMA - Journal of Land Use, Mobility and Environment, 2023)
The social, economic, and environmental challenges imposed by the complexity of the ongoing phenomena require the rapid transformation of cities into resilient, competitive urban systems. The recent European program NextGenerationEU is oriented in this direction. It allocates the resources to turn the Covid-19 pandemic into a trigger of development through the implementation of recovery plans aimed at increasing the competitiveness of the territories involved. Hence, it is urgent to find a way not only to manage the available resources but distribute them effectively, identifying priorities of interventions. This paper examines Italian metropolitan areas to support decision-makers in the prioritization/management of urban transformations in the framework of the Italian Recovery and Resilience Plan (PNRR). 53 variables belonging to five macro-areas of competitiveness were identified and elaborated. Two composite indexes were developed to compare the cities’ actual competitive performance with the distribution of resources defined by the PNRR. The aim is to understand if the PNRR investments are consistent with the case studies assets and vocations that, if boosted, may determine their competitive development. Among the main findings, it emerged a substantial deviation between competitive performance and allocated resources, especially for southern cities which received a greater boost from the PNRR than their actual competitive potential in order to overcome the North-South existing disparities.